The Anti-Angiogenic Effects of Anti-Human Immunodeficiency Virus Drugs - Barillari, Giovanni (Frontiers in Oncology, 2020)
The growth and metastasis of malignant tumors benefit from the formation of blood vessels within the tumor area. There, new vessels originate from angiogenesis (the sprouting of pre-existing neighboring vessels) and/or vasculogenesis (the mobilization of bone marrow-derived endothelial cell precursors which incorporate in tumor vasculature and then differentiate into mature endothelial cells). These events are induced by soluble molecules (the angiogenic factors), and modulated by endothelial cell interactions with the perivascular matrix. Given angiogenesis/vasculogenesis relevance to tumor progression, anti-angiogenic drugs are often employed to buttress surgery, chemotherapy or radiation therapy in the treatment of a wide variety of cancers. Most of the anti-angiogenic drugs have been developed to functionally impair the angiogenic vascular endothelial growth factor: however, this leaves other angiogenic factors unaffected, hence leading to drug resistance and escape. Other anti-angiogenic strategies have exploited classical inhibitors of enzymes remodeling the perivascular matrix. Disappointingly, these inhibitors have been found toxic and/or ineffective in clinical trials, even though they block angiogenesis in pre-clinical models. These findings are stimulating the identification of other anti-angiogenic compounds. In this regard, it is noteworthy that drugs utilized for a long time to counteract human immune deficiency virus (HIV) can directly and effectively hamper molecular pathways leading to blood vessel formation. In this short review the mechanisms leading to angiogenesis and vasculogenesis, and their susceptibility to anti-HIV drugs will be discussed.